ER−/PR+ breast cancer: A distinct entity, which is morphologically and molecularly close to triple‐negative breast cancer. Issue 1 (18th March 2021) - Beltjens, Françoise; Molly, Damien; Bertaut, Aurélie; Richard, Corentin; Desmoulins, Isabelle; Loustalot, Catherine; Charon‐Barra, Céline; Courcet, Emilie; Bergeron, Anthony; Ladoire, Sylvain; Jankowski, Clémentine; Boidot, Romain; et al.
Abstract: Determining the status of steroid hormone receptors [oestrogen (ER) and progesterone receptors (PR)] is a crucial part of the breast cancer workup. Thereby, breast cancers can be classified into four subtypes. However, the existence of ER−/PR+ tumours, often reported to be ill‐classified due to technical errors, remains controversial. In order to address this controversy, we reviewed the hormone receptor status of 49 breast tumours previously classified as ER−/PR+ by immunohistochemistry, and compared clinical, pathological and molecular characteristics of confirmed ER−/PR+ tumours with those of ER+ and triple‐negative tumours. We unequivocally confirmed the ER−/PR+ status in 27 of 49 tumours (0.3% of all breast cancers diagnosed in our institution between 2000 and 2014). We found that ER−/PR+ were morphologically and histologically similar to triple‐negative tumours, but very distinct from ER+ tumours, with more aggressive phenotypes and more frequent basal marker expression than the latter. On the molecular level, RNA sequencing revealed different gene expression profiles between the three groups. Of particular interest, several genes controlled by the suppressor of zest 12 (SUZ12) were upregulated in ER−/PR+ tumours. Overall, our results confirm that ER−/PR+ breast cancers are an extremely rare but 'real' tumour subtype that requires careful diagnosis and has distinct features warranting different responsiveness to therapies and different clinical outcomes. Studies on larger cohorts are needed to further characterise these tumours. The likely involvement of SUZ12 in their biology is an interesting finding which may – in a long run – give rise to the development of new therapeutic alternatives. Abstract : What's new? Expression levels of receptors for estrogen (ER) and progesterone (PR) on breast tumor cells are key determinants of breast cancer classification. In particular, ER/PR status potentially defines four breast cancer subtypes, the existence of one of which, ER‐/PR+ tumors, remains controversial. In this study, the authors compared clinical, pathological, and gene expression characteristics of ER‐/PR+ breast tumors to characteristics of triple‐negative and ER+ tumors. Notably, ER‐/PR+ tumors differed molecularly from triple‐negative and ER+ tumors, in addition to exhibiting more aggressive phenotypes than ER+ tumors. The data indicate that although rare, ER‐/PR+ tumors are an authentic subtype of invasive breast cancer.